Analiza czynnikowa z wykorzystaniem środowiska R - Sztemberg-Lewandowska, Mirosława (Factor Analysis with R Environment, 2008)
Factor analysis is a data reduction technique which takes a number of different variables and attempts to identify underlying relationship which may be presented. In the factor analysis an investigator is interested in explaining the relationships within his data set in terms of the smallest number of independent summary variables. In other words you identify some hidden basic variables as combinations of the variable observed. In this article the author presents methods of extracting initial factors, rotation and determining a number of factors using R system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 152-164